(untitled) (Med Phoenix, 2018)
Background: Cervical lymphadenopathy is one of the most frequent clinical manifestations of patients attending outpatient department. The etiology of cervical lymphadenopathy varies from inflammatory condition to malignant lesion. Fine needle aspiration cytology (FNAC) is a safe, easy and quick diagnostic technique. It has become the first line of investigation in the evaluation of lymphadenopathy. The objective of this study was to evaluate the spectrum of lesions in cervical lymphadenopathy and role of FNAC in the diagnosis of cervical lymphadenopathy. Methods: This study was conducted over a period of two years (May 2015 to May 2017). 206 patients with cervical lymphadenopathy were included in the study. Results: Most of the cases were non-neoplastic (91.74 %) whereas (8.26 %) cases were neoplastic. The most common cause of non-neoplastic lymphadenopathy was reactive lymphadenitis. Histocytological correlation was done in 32 cases. The diagnostic accuracy of FNAC for metastatic carcinoma and reactive lymphadenitis was 100% and 93.75% respectively. Conclusions: FNAC is a safe, cost effective and reliable procedure to diagnose the causes of cervical lymphadenopathy. Med Phoenix. Vol. 3, Issue. 1, 2018, Page: 36-40